Apnea in Beach-Chair Position Status Post Interscalene Block: A Simulation Case for Anesthesia Residents - Tyler Voigt; Allison Wagner; Clark Obr; Tejinder Swaran Singh (Association of American Medical Colleges, 2016)
Abstract Introduction Regional anesthesia is commonly performed for orthopedic operations, especially in situations when general anesthesia is preferably avoided. Anesthesia residents should understand the complications of regional procedures and should know how to treat them if treatment is warranted. This simulation involves a 60-year-old man who became apneic in the beach-chair position following an interscalene block for rotator cuff repair. It presents trainees with the opportunity to further their learning with regard to perioperative management and associated complications of patients receiving brachial plexus blocks. Methods This simulation is designed to be delivered in a single, 1-hour session. Materials contained within this simulation include a case template, a checklist of critical actions, a brief summary for key takeaways, and an evaluation form. At the conclusion of this simulation and debriefing session, the learner has had the opportunity to demonstrate progress in several of the anesthesiology milestones outlined by the Accreditation Council for Graduate Medical Education and the American Board of Anesthesiology in the Anesthesiology Milestone Project as they relate to this particular clinical topic. Results At the time of this submission, a total of 15 junior residents had completed this simulation. Commonly missed critical actions included difficulty of management of analgesia in a block that is not complete and correlation between noninvasive blood pressure on the arm and cerebral perfusion pressure. Learners' comments were generally positive, indicating the residents felt this simulation was a worthwhile learning experience. Discussion The majority of anesthesia residents who have participated in this simulation were able to properly address apnea in the beach-chair position following a brachial plexus block. It is expected that this simulation will be performed approximately 15-20 times annually.